2001
DOI: 10.1007/s00109-001-0312-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of Greek nondeletional hereditary persistence of fetal hemoglobin and β-thalassemia compound heterozygotes

Abstract: The coexistence of beta- and gamma-globin gene mutations in the compound heterozygous state presents a rare in vivo model that provides important data on gene regulation of clinical interest. In this unique comparative study we present the hematological, biosynthetic, and molecular data from six adult compound heterozygotes for the Greek nondeletional hereditary persistence of fetal hemoglobin (nd-HPFH, Agamma-117 G-->A) and four frequent beta-thalassemia mutations (IVS I-110 G-->A, Cd 39 C-->T, IVS I-1 G-->A,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…The human ␤-globin locus has been extensively studied as a paradigm for genetic regulation of lineage-and stage-specific gene expression (42), as well as for its clinical relevance to ␤-globin disorders. Elucidation of the molecular basis for ␥-globin gene silencing during definitive erythropoiesis in particular has been the focus of intense investigation, since coinheritance of genetic conditions that confer elevated ␥-globin synthesis alleviates many symptoms and at least some of the pathology associated with inherited ␤-globin disorders (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…The human ␤-globin locus has been extensively studied as a paradigm for genetic regulation of lineage-and stage-specific gene expression (42), as well as for its clinical relevance to ␤-globin disorders. Elucidation of the molecular basis for ␥-globin gene silencing during definitive erythropoiesis in particular has been the focus of intense investigation, since coinheritance of genetic conditions that confer elevated ␥-globin synthesis alleviates many symptoms and at least some of the pathology associated with inherited ␤-globin disorders (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of post-transcriptional regulation of HbF expression has been suggested before. 25,26 However, it has not been supported by comprehensive experimental data and, as a consequence, has remained largely overlooked. The Corfu case is not the only example of a mutation displaying low HbF expression in the heterozygote state and very high HbF expression in a compound heterozygote background.…”
Section: Discussion the Corfu Paradoxmentioning
confidence: 99%
“…The human ␤-globin locus is composed of ε-(embryonic), G␥-and A␥-(fetal), and ␦-and ␤-globin (adult) genes, which are spatially arranged from 5Ј to 3Ј and developmentally expressed in the same order (72). The elucidation of the molecular basis for ␥-globin silencing in the adult stage in particular has been the focus of intense investigation, since it has been observed that coinheritance of genetic conditions that confer elevated ␥-globin synthesis can significantly alleviate the symptoms of ␤-globin disorders (44,56). Previously, several adult-stage ␥-globin repressors have been identified, such as BCL11A and SOX6 that physically interact with each other to repress the ␥-globin genes (67,84,86), as well as Ikaros (42) and GATA1 (20).…”
mentioning
confidence: 99%